Spectral study to determine type of oil products and the mixing rates between them - Assmat. R. Al-Hadeethi; Hamid. S. Al-Jumaili; M. M. Sirhan (مجلة بغداد للعلوم)
In this paper we have measured the spectral absorption for some oil products and there mixtures within range (300-700nm). These products are (gas oil, kerosene, gasoline).  The mixing ration includes the values (0:10,2:10,4:10,6:10,8:10,10:10).  From the absorption spectrum with wave length we can determine the location and value of absorption peaks. Then we compare between mixed and unmixed Iraqi oil products.  We were able also to determine the quantity mixture from the location and absorption values.  We found that there are interactions between some materials produce another type with different properties subsequently it will give negative result when it used in oil machines.  The density of the other kind of products was changed during the mixing process only.We have explained the results according to the spectral absorption of the oil products.